2021
DOI: 10.1038/s41418-021-00802-2
|View full text |Cite
|
Sign up to set email alerts
|

β-arrestin 2 stimulates degradation of HIF-1α and modulates tumor progression of glioblastoma

Abstract: The basic function of β-arrestin 2 (Arrb2) is to negatively regulate the G-protein-coupled receptor signaling pathway through facilitating receptor desensitization and internalization. Arrb2 has also been reported to play various roles in cancer pathology including the proliferation, migration, invasion, metastasis, and apoptosis of solid tumors. However, the molecular mechanisms underlying the tumorigenic capacities of Arrb2 have not been elucidated. Here, we show a novel function of Arrb2: Arrb2 facilitates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…The overexpression of β-arrestin 2 in GBM slows HIF-1α signaling, preventing tumor growth and angiogenesis. Conversely, knockdown of β-arrestin 2 increases HIF-1α levels and lessens survival in patients with GBM [ 40 ]. Studies have also indicated that nociceptin receptor (NOPr), a G protein-coupled receptor that is significantly expressed in GBM, mediates nociceptin through the β-arrestin 2/PKC/extracellular signal-regulated kinase 1/2 (Erk1/2) pathway to hinder proliferation, migration, and inflammatory signaling in lipopolysaccharide-stimulated U87 cells [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overexpression of β-arrestin 2 in GBM slows HIF-1α signaling, preventing tumor growth and angiogenesis. Conversely, knockdown of β-arrestin 2 increases HIF-1α levels and lessens survival in patients with GBM [ 40 ]. Studies have also indicated that nociceptin receptor (NOPr), a G protein-coupled receptor that is significantly expressed in GBM, mediates nociceptin through the β-arrestin 2/PKC/extracellular signal-regulated kinase 1/2 (Erk1/2) pathway to hinder proliferation, migration, and inflammatory signaling in lipopolysaccharide-stimulated U87 cells [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to arrest HIF-1α activity, and the growth and angiogenesis of GBM cells. High β-arrestin 2 expression levels correlate with better survival in patients with GBM [ 40 ]. Thus, BCAS1-SV1 may modify β-arrestin 2 activity to mediate the proliferation and migration of GBM.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely accepted that many transcription factors are highly expressed in GBM, including SOX2, HIF-1α, and c-Myc ( Zhang et al, 2011 ; Man et al, 2018 ; Zhou et al, 2016 ; Zheng et al, 2015 ; Bae et al, 2021 ). These transcription factors are not only involved in promoting the initiation of the transcriptional process of protein-coding genes but are also required for the initiative transcription of noncoding genes, including lncRNAs.…”
Section: Generally Molecular Basis Of Lncrnasmentioning
confidence: 99%
“…Promotes cell proliferation and migration potential (Masannat et al, 2018) Bladder cancer Inhibits stem-cell phenotype and enhances chemotherapy response (Kallifatidis et al, 2019) Glioblastoma Obstructs via inhibition of HIF-mediated angiogenesis (Bae et al, 2021) since it has overexpression decreases the expression level of phosphorylated and non-phosphorylated PI3K/AKT and Bcl-2, and increases the appearance level of apoptotic Bax and caspase-3 in cancer cell lines (Y. Jiang et al, 2020).…”
Section: Renal Cancermentioning
confidence: 99%